Information security management systems (ISMS) and computer security self-efficacy (CSSE) model comparison - Al-Shawabkeh M.; Azman N.; Madihah Mohd Saudi; Najwa Hayaati Mohd Alwi (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA